ANALYSIS OF ECONOMIC ACTIVITY AS THE BASIS FOR THE ADOPTION OF MANAGEMENT DECISIONS - A.A. Kurmanalina; A.I. Omarova; A.M. Sapargali (Academic Journal of Physical and Chemical Sciences, 2019)
Analysis of the economic activities of the organization is the basis for making management decisions in business. To justify management decisions, problems should be identified, production and financial risks should be assessed, possible consequences of the decisions made should be determined. As a general indicator of the financial and economic activity of the enterprise, the level of profitability is used, which is calculated as the ratio of net profit to the sum of fixed and circulating production assets.